Impact of distinct antiviral treatment regimens on the long-term outcome after HCV cure – Data from the German Hepatitis C-Registry (DHC-R) - Ohlendorf, Valerie; Serfert, Yvonne; Buggisch, Peter; Mauss, Stefan; Klinker, Hartwig; Teuber, Gerlinde; Cornberg, Markus; Tomasiewicz, Krzysztof; Wedemeyer, Heiner (Zeitschrift für Gastroenterologie, 2025)
Direct-acting antiviral (DAA) regimens for the treatment of hepatitis C virus (HCV) infection are endowed with sustained virological response (SVR) rates >95%. However, HCV cure does not completely eliminate the risk of hepatocellular carcinoma (HCC) development and liver decompensation. The present study investigated the impact of the administered DAA regimen on clinical long-time outcomes after SVR.Matched-pair survival analyses of 5802 chronically HCV infected patients from the German Hepatitis C-Registry compared the incidence of liver-related events 2.5 years after SVR in patients receiving either sofosbuvir (SOF)-based treatment or NS3/NS4A-protease inhibitor (PI)-containing DAA regimens. Hypothesis driven logistic regression analyses were performed to identify independent predictors for the occurrence of liver-related events.Matched-pair survival analyses revealed a borderline significant difference in the incidence of liver-related endpoints (except of HCC development) in patients receiving SOF-based treatment (4.1%) compared to PI-containing DAA regimens (2.6%) 2.5 years after SVR (p=0.061). Numerically, a trend towards a benefit of PI-based DAA treatment was observed (PI 65 events vs SOF 102 events). Hypothesis driven logistic regression analyses could not confirm SOF-based treatment as an independent predictor for the occurrence of liver-related events after HCV cure (p=0.072, OR=0.670).The incidence of liver-related events 2.5 years after HCV cure did not differ significantly between SOF-based DAA treatment and PI-containing regimens. However, numerically a trend towards a benefit of PI-based DAA treatment was observed. Therefore, a minor effect of the applied DAA regimen on the long-term incidence of liver-related events cannot be excluded.
Keywords: Liver; hepatitis C; viral hepatitis; direct acting antivirals (DAA); hepatocellular carcinoma; sustained virological response; liver cirrhosis; long-term follow up; survival